Bolus rheology and ease of swallowing of particulated semi-solid foods as evaluated by an elderly panel. Issue 10 (16th September 2020) - Ben Tobin, Aarti; Mihnea, Mihaela; Hildenbrand, Marie; Miljkovic, Ana; Garrido-Bañuelos, Gonzalo; Xanthakis, Epameinondas; Lopez-Sanchez, Patricia
Abstract : Preparation of a bolus is a complex process with both food comminution and degree of lubrication with saliva playing an important role in a safe swallow. Abstract : Preparation of a bolus is a complex process with both food comminution and degree of lubrication with saliva playing an important role in a safe swallow. Swallowing disorders i.e. dysphagia, are especially present among the elderly population and often lead to choking and further health complications. The aim of this research was to investigate the relationship between the perception of ease of swallowing in the elderly and the rheological parameters of particulated foods, using broccoli purees as a model system. Particulated foods can be described as a concentrated dispersion of plant particles in a fluid phase. The effect of the fluid phase (Newtonian vs . shear thinning) and dispersed phase (plant particles with different size distribution and morphology) on the rheological properties of simulated boli was studied by characterising shear viscosity, viscoelasticity, yield stress, extensional viscosity and cohesiveness. Ease of swallowing and mouthfeel were evaluated by a semi trained healthy elderly panel ( n = 19, aged 61 to 81). Ease of swallowing was correlated with the presence of yield stress and extensional viscosity in the bolus, characteristic of boli with xanthan gum as the fluid phase. Although the properties of the fluid phase played a dominant role in the ease of swallowing, compared to the dispersed phase, both components played a role in the rheological properties of the bolus and the perception of ease of swallowing by the elderly panel. These results provide insights into the design of personalised foods for populations with specific needs such as those suffering from swallowing disorders.